Knowledge and Attitude on Dementia among Nursing Students of Pokhara - Thapa, Monika; Gurung, Bishnu (NPRC Journal of Multidisciplinary Research, 2025)
Dementia cases are rising rapidly worldwide, prompting the World Health Organization (WHO) to recognize dementia as a public health priority. As primary caregivers, nursing students play a crucial role in dementia care, where their knowledge and attitude significantly impact the quality of care provided. This study aimed to assess the knowledge and attitude of nursing students in Pokhara regarding dementia.A descriptive cross-sectional study was conducted among 121 third-year PCL nursing students from three nursing colleges: Fishtail Nursing Campus, Charak Academy, and Fewa City Institute of Medical Science. Simple random sampling was used to select the colleges, and all eligible nursing students were included using a complete enumeration method. Data were collected using a self-administered structured questionnaire, with standardized tools such as the Alzheimer’s Disease Knowledge Scale (ADKS) and the Dementia Attitude Scale (DAS). The collected data were entered into the Statistical Package for Social Sciences (SPSS) version 16 and analyzed using descriptive statistics (frequency, percentage, mean, and standard deviation). Inferential statistics, including the t-test, were used to assess differences in knowledge and attitude scores based on background variables. Pearson’s correlation coefficient was applied to examine the relationship between knowledge and attitude regarding dementia.The study found that the mean knowledge score was 15.64, while the mean attitude score was 95.61. No statistically significant differences were observed in knowledge and attitude scores across the variables. Additionally, there was no correlation between knowledge and attitude toward dementia (Pearson Correlation Coefficient = -0.007, p-value = 0.941).The findings indicate that nursing students performed best in the assessment and diagnosis domain but scored lowest in the symptoms domain of dementia knowledge. Their overall attitude toward dementia was moderately positive. However, enhancing nursing students' knowledge while maintaining a positive attitude is essential for ensuring high-quality care for individuals with dementia.